THE INFLUENCE OF CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURN OVER, AND FIRM SIZE ON RETURN ON EQUITY IN PROPERTY COMPANIES - Viona Avelina; Jhon Lismart Benget. P.; Jessica Jessica; Aprilyani Aprilyani; Calvin Nico Adryan; Belthasar Trito Siahaan (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Objective from study This that is To use see the influence of Current Ratio, Debt to Equity Ratio, Total Assets Turn Over and firm size on company sector Property listed on the Indonesia Stock Exchange Period 2017-2021 is good in a manner Partial And simultaneous . Company founded generally aim For obtain maximizing profits for survival _ life his company And capable develop company that well . _ All companies on basically carry out various activity good character _ operational or non- operational To use gain . Population is all company sector Property on the IDX for the 2017-2020 period namely as many as 65 companies And the sample with a total of 60 units of analysis . Method study apply technique analysis multiple linear regression . Results study is Current Ratio and Firm size have no effect on Return On Equity. Debt to Equity Ratio and Total Asset Turn Over effect on Return On Equity. Current Ratio, Debt to Equity Ratio, Total Assets Turn Over, and Firm Size have an effect against Return On Equity on company sector properties listed on the Indonesia Stock Exchange for the 2017-2021 period